2002
DOI: 10.1046/j.1439-0442.2002.00475.x
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Dermatitis and Nephropathy Syndrome. Clinical and Pathological Features of Cases in the United Kingdom (1993–1998)

Abstract: This paper documents the salient clinical and pathological features of porcine dermatitis and nephropathy syndrome (PDNS) in 96 pigs submitted from 55 units in the UK from 1993 to 1998. This series of cases pre-dated the emergence of post-weaning multisystemic wasting syndrome (PMWS) in the UK. The morbidity during outbreaks was 1% or less. Affected pigs ranged from 14 to 70 kg in weight and most died after a short clinical illness. Fifty-five pigs had multifocal or coalescing erythematous skin lesions, some p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
1
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 11 publications
1
15
1
4
Order By: Relevance
“…However, the morphologic features of glomerular lesions of PDNS are quite different from those found in the present case, since glomerulonephritis of PDNS is characterized by severe necrotizing changes and fibrinous exudates [7,12]. In the present case, the immunohistochemical reactions to the antigens against PRRSV or PCV-2 which are involved in PDNS [2,9], were negative.…”
contrasting
confidence: 75%
“…However, the morphologic features of glomerular lesions of PDNS are quite different from those found in the present case, since glomerulonephritis of PDNS is characterized by severe necrotizing changes and fibrinous exudates [7,12]. In the present case, the immunohistochemical reactions to the antigens against PRRSV or PCV-2 which are involved in PDNS [2,9], were negative.…”
contrasting
confidence: 75%
“…Several pathogens including viruses (PRRSV) 22,130 and bacteria (Pasteurella multocida, Streptococcus suis type 1 and 2, Escherichia coli, Proteus sp., Haemophilus parasuis, Actinobacillus pleuropneumoniae, Bordetella bronchiseptica, Arcanobacterium pyogenes, Staphyloccoccus aureus, or Salmonella sp.) 74,131 have been incriminated as possible etiologies for PDNS.…”
Section: Pcv2-associated Pdnsmentioning
confidence: 99%
“…PCVAD encompasses a group of complex, multifactorial diseases, of which porcine multisystemic wasting syndrome (PMWS) and porcine dermatitis and nephropathy syndrome (PDNS) are common syndromes (7,49,52,53). Even though Krakowka et al (25) reported the appearance of PDNS in gnotobiotic pigs in the absence of PCV2, pigs with clinical PDNS possess high levels of PCV2-specific antibodies, which are implicated in disease progression (53). In 2008, poor growth performance in herds without overt clinical signs was reported as another manifestation of PCVAD (20).…”
mentioning
confidence: 99%